RESPONSE. - Swartz, David R. (Fides et historia, 2015)
The author responds to comments on his book "Moral Minority: The Evangelical Left in an Age of Conservatism." He examines various judgments about the coherence of evangelicalism and the measurement of the movement's success by analyzing its coherence or its electoral impact. He describes the relationship between the evangelical left and the U.S. Democratic Party. He also discusses the issue of international evangelicalism.